NECK PAIN IN MOVEMENT DISORDERS: BURDEN OF CERVICAL DYSTONIA - Raisa, Neila (Journal of Pain, Headache and Vertigo, 2024)
Cervical dystonia (CD) is a form of focal dystonia clinically manifesting as sustained or intermittent contractions of the neck muscles, resulting in abnormal movements, repetitive postures, or both, often leading to pain in most patients. This condition not only impacts patients' mobility, self-care, and daily activities but also presents with sensory and cognitive changes, contributing significantly to disability and social isolation. Despite being the most common type of focal dystonia with an incidence of 4.98/100,000 in Europe, CD is often underdiagnosed or misdiagnosed, leading to delays in appropriate treatment. This paper explores the epidemiology, clinical diagnosis, and assessment of pain in CD, highlighting the challenges in diagnosing this condition due to its similarity to other movement disorders.